Pengaruh Quick Response Code Indonesian Standard (QRIS) pada Usaha Mikro, Kecil, dan Menengah (UMKM) dalam Mendukung Inklusi Keuangan di Kabupaten Toraja Utara - Yemima Tandibua; Grace Siriati Mengga; Yohanis L Tadung (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to analyze the effect of using the Quick Response Code Indonesian Standard (QRIS) on improving financial inclusion among Micro, Small, and Medium Enterprises (MSMEs) in North Toraja Regency. The research is motivated by the rapid development of digital payment systems, which have not been optimally adopted by MSMEs in tourism areas. QRIS, as a non-cash payment innovation, is expected to expand access tofinancial services, enhance transaction efficiency, and encourage MSMEs’ participation in the formal financial system. This study employs a quantitative approach using a survey method involving 35 handicraft MSMEs in the Ke’te Kesu’ tourism area, selected through a saturated sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed with SPSS version 25 through validity and reliability tests, descriptive analysis, classical assumption tests, and simple linear regression. The results indicate that QRIS usage has a positive and significant effect on financial inclusion, with a correlation coefficient (R) of 0.758 and a coefficient of determination (R²) of 0.575. The t-test shows a significance value of < 0.05. These findings support the Financial Deepening theory and the financial inclusion concept, which emphasize access, affordability, and usage of financial services. Thus, QRIS serves as an important instrument in promoting digital transformation and enhancing financial inclusion among MSMEs in North Toraja Regency.